Physical Condition Athletes of Sepak Takraw Club at UNIMED - Mawardinur (Jurnal Master Penjas & Olahraga, 2025)
Athlete performance fundamentally depends on physical conditioning, which remains essential for competitors seeking excellence in their respective disciplines. Each sport presents unique physiological demands that athletes must address through targeted development of their bodily capabilities. This research investigated the fitness characteristics of male sepak takraw players from Unimed's club (USTC). Using quantitative descriptive analysis, researchers assessed five athletes chosen through purposive sampling methods. Physical evaluations measured multiple attributes including muscular strength, velocity, coordination, explosive capacity, and cardiovascular stamina. Findings revealed that participants demonstrated moderate fitness levels, with 60% achieving satisfactory ratings across measured parameters. These outcomes provide valuable insights for coaches and trainers to refine their preparation strategies, adjust program delivery, and optimize conditioning approaches throughout training cycles. The data supports evidence-based decision-making in athlete development planning.